SCIENTIFIC RESEARCH PRACTICE IN EDUCATIONAL PROGRAMS FOR THE TRAINING OF MASTERS OF PHILOLOGY - Iryna Prozhohina (Borys Grinchenko Kyiv Metropolitan University, 2022)
Research practice as a component of the educational programs of the specialty «Philology» at the master's degree in higher education is analyzed, namely its place in the system of specialists' research skills formation. Descriptions of 80 educational programs for the preparation of masters in philology, introduced in 2019-2022 in six universities of Ukraine, were analyzed, particularly the presence of practice(s), which correlates with the defined purpose of these programs from the point of view of the masters' scientific and research skills formation. It was found that some educational programs don't include this kind of practice. The existing practices have various names not only in different universities but also in the same one; some of the names do not reflect the essence of this practice as scientific and research (production, pre-diploma, etc.). It has been proved that research practice should be a compulsory component of the master's educational programs in philology. The purpose of such practice should be subordinated to the broader task of forming the research competence of the philologist, taking into account the professional suitability of the future specialist, which is not limited to teaching philological disciplines in secondary or higher education. The content of the philological master's practice should be consistent both with the standard of higher education in philology for obtaining the master's degree and with the description of a specific educational program. The volume in ECTS credits (in some programs also the duration) of practice(s) has been clarified. It is suggested to conduct this practice in the middle of the curriculum - for educational and scientific programs at the end of the second semester or after it; so that the practice becomes a connecting link between the studied theoretical courses and future independent research, especially a master's thesis.